The demographic profile and psychosocial history of a group of convicted perpetrators of the rape of children under the age of three years. - Kleijn, Amelia Ann (My University, 2010)
Sexual crimes against women and children are not new social phenomena. South Africa continues to experience high rates of such crimes against women and children, including rape, abuse, indecent assault and incest, with media reports highlighting the rape of children under the age of three years old. The current research was triggered by the call from various professionals to try and understand why such acts occur. The main aim of this research was, through the identification and description of the demographic profile and psychosocial history of ten convicted perpetrators serving correctional sentences for the rape of children under the age of three years, to develop an understanding of the circumstances in the psychosocial histories of these perpetrators which may have led them to commit such acts. The research design for the study was qualitative and followed phenomenological and ethnomethodological approaches that aimed to understand and interpret meaning that respondents ascribed to their lives. Grounded theory was used to analyze data obtained from a series of semi-structured interviews conducted with ten men serving correctional sentences for the rape of children under the age of three years. The data were categorized into a coding paradigm, which led to the formation of a proposition. The proposition suggests that the respondents in the current study, who have raped children under the age of three, have childhood psychosocial histories associated with physical and emotional abuse, as well as neglect, experienced most particularly from their mothers, within a milieu of desperate poverty. Such deprivation and maltreatment possibly led to attachment difficulties and influenced the development of adequate resilience. Similar difficulties were also noted during the respondents’ adulthood. Some unemployed men possibly rape children under the age of three years, impulsively, in response to their feelings of anger, and need for revenge, against men and women. There was no suggestion from respondents who participated in the current study that their sexual acts were in response to the “virgin-cleansing” myth. However, the small sample size in the present research means that these findings cannot be generalized to all men who rape children under the age of three years.